2022
DOI: 10.1177/00099228221094127
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional Acute Poisoning Related Emergency Department Visits in Children in a Single-Center: A Nine-Year Prospective Survey

Abstract: Pediatric morbidity due to unintentional poison exposure is a significant burden on public health. We prospectively characterize patterns of unintentional poison exposure in a single pediatric emergency department, using a detailed computerized questionnaire for all unintentional injuries admitted during 2009 to 2017. Out of 71,765 visits due to unintentional injuries, 252 children were admitted due to unintentional poison exposure. Most (198/252, 79%) were between 1 and 3 years of age. The majority of events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Acute poisoning is a major public health problem and an important reason for hospital emergency department visits (16)(17)(18)(19). In this study, we investigated the clinical and sociodemographic profiles associated with acute poisoning cases, shedding light on the trends and risk factors in Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Acute poisoning is a major public health problem and an important reason for hospital emergency department visits (16)(17)(18)(19). In this study, we investigated the clinical and sociodemographic profiles associated with acute poisoning cases, shedding light on the trends and risk factors in Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…The highest frequency of unintentional poisoning was in the age group 1-3 years. In some studies in other countries, the highest frequency of unintentional poisoning has been reported in the age group under 5 years (6, 16) or 1-3 years (31,33). In Iran, most studies have reported the highest frequency for the age group 1-3 years (19,22,34).…”
Section: Demographic Characteristics Of Patientsmentioning
confidence: 97%